IMPLEMENTASI PERFORMANCE PEDAGOGY DALAM PEMBELAJARAN MUSIK INFORMAL PADA KOMUNITAS BELAJAR MAHASISWA - Riyan Hidayatullah; Sumarti; Prisma Tejapermana; Muharsyam Dwi Anantama; Nabila Hasri Ainun (Jurusan Pendidikan Bahasa dan Seni, FKIP Universitas Lampung, 2026)
This community service activity aims to implement the Performance pedagogy approach to improve the quality of informal music learning in a student learning community at the Department of Language and Arts Education (JPBS), Faculty of Teacher Training and Education (FKIP), Universitas Lampung. The program was carried out through a workshop attended by 20 students from the Music Education, Indonesian Language and Literature Education, and English Education study programs. Activities included conceptual presentations, demonstrations, ensemble practice, and musical performance. Evaluation was conducted using pre-test and post-test via the Kahoot application. Results showed a significant increase in participant understanding, from 36% correct answers in the pre-test to 84% in the post-test. The result shows an improvement of 48%. Qualitative reflections indicated a shift in participants' orientation toward viewing performance not as an end product of learning, but as an integral and meaningful part of the learning process itself. This program demonstrates that the Performance pedagogy approach is effective and relevant as a model for strengthening student learning communities through informal music learning. Kegiatan pengabdian kepada masyarakat ini bertujuan mengimplementasikan pendekatan Performance pedagogy untuk meningkatkan kualitas pembelajaran musik informal dalam komunitas belajar mahasiswa di Jurusan Pendidikan Bahasa dan Seni (JPBS), Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lampung. Program ini dilaksanakan melalui kegiatan lokakarya yang diikuti oleh 20 mahasiswa dari Program Studi Pendidikan Musik, Pendidikan Bahasa dan Sastra Indonesia, dan Pendidikan Bahasa Inggris. Kegiatan meliputi pemaparan konsep, demonstrasi, praktik ansambel, dan pertunjukan musik. Evaluasi dilakukan melalui pretest dan posttest menggunakan aplikasi Kahoot. Hasil evaluasi menunjukkan adanya peningkatan pemahaman peserta yang signifikan, dari 36% jawaban benar pada pretest menjadi 84% pada posttest, atau mengalami peningkatan sebesar 48%. Refleksi kualitatif juga menunjukkan adanya pergeseran orientasi peserta dalam memandang pertunjukan, dari sekadar hasil akhir pembelajaran menjadi bagian yang integral dan bermakna dari proses pembelajaran itu sendiri. Program ini menunjukkan bahwa pendekatan Performance pedagogy efektif dan relevan sebagai model untuk memperkuat komunitas belajar mahasiswa melalui pembelajaran musik informal.